The Natural History of Cerebellar Hemangioblastomas in von Hippel-Lindau Disease - Slater, Andrew; Moore, Niall R.; Huson, Susan M. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Cerebellar hemangioblastomas (HBs) are traditionally classified into different morphologic types: cystic and solid. We have observed the progression from solid to cystic and have reviewed the cases seen at the regional von Hippel-Lindau (VHL) clinic to document the frequency of this progression.METHODS: A retrospective review of the notes and images of all patients with VHL disease seen at a regional referral clinic since its inception in 1991. Sporadic HBs were not included in this study.RESULTS: In eight patients, a total of 28 tumors were detected. Fourteen of these had or developed cysts. Of the 14 cystic tumors, eight increased in size over the follow-up period. Of the 14 solid tumors, only one increased in size without cystic change. In four patients, the tumor progressed from a cerebellar nodule to an enlarging cyst with a nodule, with the subsequent development of symptoms requiring surgical excision.CONCLUSION: We have demonstrated that, in VHL, cerebellar HBs begin as nodules, and some subsequently develop enlarging cysts that cause pressure symptoms. In our patient population, tumors that remained solid were asymptomatic and well tolerated in the cerebellum.